Some Data on East Aukštaitija Writers - Riškus, Jonas; Urbanavičiūtė, Zana (Literatūra, 1967)
The correspondence between Ivan Lobojko (professor at Wilna University in the beginning of the 19th century) and N. P. Rumiantsev reveals new facts and data about certain Lithuanian culture workers of the 19th century.Usually Kajetonas Nezabitauskis was considered the author of the manuscript Polish-Lithuanian dictionary (dated 1823). Lobojko's letters make it possible to put forward a new supposition: Kiprijonas Nezabitauskis (not Kajetonas, his brother) is the only author of this dictionary mentioned by the correspondents.We learn that the author used only contemporary words for his dictionary. The manuscript, formerly kept by Warsaw University Library, got lost during World War II. If found, this manuscript would serve as a document showing the actual state of Lithuanian lexics in the beginning of the 19th century.The letters also provide new data concerning Dionizas Poška, his dictionary, and his collection of antiquities.This correspondence reflects how materials about Lithuania and the Lithuanian language were being collected in the twenties of the 19th century.
Keywords: -